The morningside : a novel - Obreht, Téa (Random House, 2024)
"When Silvia and her mother finally land in a place called Island City, after being expelled from their ancestral home in a not-too-distant future, they end up living and working at The Morningside, a crumbling luxury tower where Silvia's aunt, Ena, has been serving as the superintendent. Silvia feels unmoored in her life because her mother has been so diligently secretive about the family's past. But in Ena there is an opening: a person willing to give a young girl glimpses into the folktales of her demolished homeland in the Old World, a place of natural beauty and communal spirit that is lacking in Silvia's new home. As Silvia begins seeing the world with magical possibilities, she becomes obsessed with the mysterious woman who lives in the penthouse of the Morningside, with three massive Rottweilers who may or may not be more than they appear. Silvia's mission to unravel the truth about this woman's life, and her own haunted past, will transform her own life in the most unexpected of ways"--